Primary User Emulation Attacks Analysis for Cognitive Radio Networks Communication - Wang Shan-Shan; Luo Xing-Guo; Li Bai-Nan (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
Cognitive Radio Network is an effective technology and a hot research direction which can solve the problem of deficient resource and revolutionize utilization. And its safety technology attracts more and more researches. Primary user emulation attacks (PUEAs) are typically easy and largely affecting. PUEAs come from both malicious misbehavior secondary users (MMUs) and selfish misbehavior secondary users (SMUs). The former is studied much more deeply than the later one. Distinguishing MMU and SMU, we propose a Four Dimensional Continuous Time Markov Chain model to analyze the communication performance of normal secondary users under PUEAs, and typically affected by SMUs. Furthermore, we compare several PUEA detection schemes. The emulation results indicate that the SMU detection mechanism is essential for the PUEA detection schemes, which can improve the detection effects largely. DOI: http://dx.doi.org/10.11591/telkomnika.v11i7.2840